mHealth-based intervention by community workers to support family caregivers of persons with dementia living at home: study protocol for a cluster randomised controlled trial - Pankaj Bhardwaj; Hanne Konradsen; Manoj Kumar Gupta; Abhik Sinha; Nitin Kumar Joshi; Suresh K Sharma; Naresh Nebhinani; Marie Tyrrell; Åsa G Craftman; Zarina Nahar Kabir (BMJ Open)
Background India is undergoing a significant demographic shift with a growing older population, leading to an anticipated increase in people with dementia. Family caregivers, who are predominantly informal, carry the burden of care within households, facing numerous challenges that impact their well-being. Despite the cultural emphasis on family support, there is a lack of targeted interventions for caregivers in India. The WHO emphasises the importance of caregiver support, and recent advancements in information and communication technology, particularly mobile health (mHealth), offer promising avenues to address this need. This study protocol outlines an Indo-Sweden collaborative effort, funded by Indian Council of Medical Research (ICMR) Forte, to develop and assess the effectiveness of a mHealth application designed to improve caregiving skills, reduce caregiver burden and support family caregivers of persons with dementia.Methods and analysis The study will be conducted through a community-based cluster randomised controlled trial in Jodhpur, Rajasthan, with Accredited Social Health Activists (ASHAs) serving as the unit of randomisation. The methodology includes several key phases: a needs assessment to understand caregiver requirements, the development of the mHealth application, comprehensive training for ASHAs and a thorough evaluation of the intervention’s impact.The effectiveness of the intervention will be measured through quantitative assessments of stress reduction, depressive symptoms and quality of life improvements, alongside qualitative insights from stakeholders. Additionally, usability and cost analyses will be conducted to evaluate the practicality and economic feasibility of the intervention.The expected outcomes of this study include the creation of a scalable mHealth platform that facilitates remote support, bridges geographical gaps and enhances the well-being of caregivers in India’s evolving healthcare landscape.Ethics and dissemination Ethical approval has been obtained from the Institutional Ethical Committee of AIIMS Jodhpur (AIIMS/IEC/2022/4245).Trial registration number Clinical Trials Registry: CTRI/2022/12/048320.